Drumul și castrul roman de la Copăceni (com. Racovita, jud. Vâlcea). Reevaluarea recentă a unor monumente uitate. - Ovidiu Țentea; Vlad-Nicolae Călina; Ioana-Iulia Manea (Cercetări Arheologice, 2022)
The purpose of this study is to make known the recent research results, but especially to highlight the importance of these results both scientifically and in a broader context, determined by the submission for inscription on the UNESCO World Heritage List (Frontiers of the Roman Empire), as well as the project and commencement of works for the A 1 highway, Sibiu-Pitești, segment 2 (Boița-Cornetu). The paper provides the basis necessary to justify the nomination to the World Heritage List, as well as the technical support required for preservation and enhancement actions by the highway constructor. We will briefly outline the results of the recent documentation carried out within the framework of the National LIMES Programme in the Racovița and Copăceni forts, together with the associated roman civil settlements and other archaeological features.